Pengaruh Pendidikan Kewirausahaan , Lingkungan Keluarga Dan Efikasi Diri Terhadap Intensi Berwirausaha Mahasiswa Di STKIP PGRI Tulungagung (Studi Pada Mahasiswa Pendidikan Ekonomi Tahun 2019-2020) - Okem Boy Omardi; Abu Talkah; Ahsin Daroini (Otonomi, 2020)
This study aims to determine (1) the effect of entrepreneurship education on entrepreneurship intentions of Economic Education students at STKIP PGRI Tulungagung Academic Year 2019/2020; (2) the influence of the family environment on the intentions of entrepreneurship in Economic Education students at STKIP PGRI Tulungagung Academic Year 2019/2020; (3) the effect of self-efficacy on the entrepreneurship intentions of Economic Education students in STKIP PGRI Tulungagung Academic Year 2019/2020; (4) the influence of entrepreneurship education, family environment and student self-efficacy on the intentions of entrepreneurship in Economic Education students at STKIP PGRI Tulungagung Academic Year 2019/2020; The data collection method used in this study uses a questionnaire / questionnaire. The population in this study were 48 students of Economic Education at STKIP PGRI Tulungagung Academic Year 2019/2020. Because this study uses population, the samples and sampling of the study were not used in this study. Data were analyzed using descriptive statistics, prerequisite tests, multiple linear regression analysis. The results of this study indicate that included in the type of quantitative research. Quantitative data analysis used is multiple linear regression and uses SPSS version 24.0 (1) the effect of entrepreneurship education, family environment and student self-efficacy on student entrepreneurship intentions with a regression coefficient of entrepreneurship education of 0.093, coefficient value of the family environment of 0.453 and value of Self-efficacy regression coefficient of 0.462 and F arithmetic> F table (91.484> 2.82); (2) entrepreneurship education has a positive effect on entrepreneurial intentions with a coefficient value of 0.093 and t arithmetic> t table (0.730 <2.01537); (3) family environment has a positive effect on entrepreneurial intentions with a regression coefficient of 0.093, t arithmetic for (5.198> t table 2.01537)) self-efficacy has a positive effect on entrepreneurial intentions with a regression coefficient of 0.093 and t arithmetic for (3.834> t table 2.01537).